Evolution of C(4) Photosynthesis in the Genus Flaveria: Establishment of a Photorespiratory CO(2) Pump([W]) - Schulze, Stefanie (American Society of Plant Biologists, 2013)
C(4) photosynthesis is nature’s most efficient answer to the dual activity of ribulose-1,5-bisphosphate carboxylase/oxygenase and the resulting loss of CO(2) by photorespiration. Gly decarboxylase (GDC) is the key component of photorespiratory CO(2) release in plants and is active in all photosynthetic tissues of C(3) plants, but only in the bundle sheath cells of C(4) plants. The restriction of GDC to the bundle sheath is assumed to be an essential and early step in the evolution of C(4) photosynthesis, leading to a photorespiratory CO(2) concentrating mechanism. In this study, we analyzed how the P-protein of GDC (GLDP) became restricted to the bundle sheath during the transition from C(3) to C(4) photosynthesis in the genus Flaveria. We found that C(3) Flaveria species already contain a bundle sheath–expressed GLDP gene in addition to a ubiquitously expressed second gene, which became a pseudogene in C(4) Flaveria species. Analyses of C(3)-C(4) intermediate Flaveria species revealed that the photorespiratory CO(2) pump was not established in one single step, but gradually. The knowledge gained by this study sheds light on the early steps in C(4) evolution.